A new device in immediately loaded implant treatment in the edentulous mandible - De Vasconcellos, Diego Klee [UNESP]; Bottino, Marco Antonio [UNESP]; Saad, Paulo Abdala; Faloppa, Flávio (My University, 2006)
Purpose: This article reports preliminary clinical results of the Speed Master system, a method for immediate loading of implants for the treatment of mandibular edentulism. Materials and Methods: Fifteen patients with edentulous mandibles were consecutively included in the study. Each received 4 implants between the mental foramina placed using the system's surgical guides. Permanent fixed prostheses fabricated over premanufactured titanium bars were attached to the implants on the day of implant placement. The patients were followed for 15 to 27 months (mean, 19 months). Peri-implant tissues were periodically evaluated. Marginal bone loss was monitored with periapical radiographs using a computerized technique. Satisfaction was assessed by means of a questionnaire. Results: The overall implant and prosthetic survival rates were 100%. At the time of the final follow-up visit, mean marginal bone loss was 1.11 mm, and bleeding on probing was not observed. Only 6.7% of the patients reported any discomfort during treatment, and all patients would recommend the procedure to others. Discussion: The immediate loading of implants placed in the edentulous mandible with the Speed Master surgical and prosthetic protocol reduces treatment time and number of surgical procedures in comparison to classic delayed loading protocols. Conclusion: The rehabilitation of the mandible with an immediately delivered occlusally loaded hybrid prosthesis supported by 4 implants does not appear to jeopardize the success of the osseointegration and represents a viable treatment option.
Keywords: Edentulous; Immediately loaded fixed prostheses; Immediately loaded implants; Mandibular implants; Single-stage implant placement; adult; aged; edentulousness; female; human; instrumentation; jaw disease; male; mandible; methodology; middle aged; osteolysis; questionnaire; radiography; time; tooth implantation; weight bearing; Adult; Aged; Alveolar Bone Loss; Dental Implantation, Endosseous; Dental Implants; Female; Humans; Jaw, Edentulous; Male; Mandible; Mandibular Diseases; Middle Aged; Questionnaires; Time Factors; Weight-Bearing